Polyvinylpyrrolidone Influences the Sol–Gel Preparation and Heat Generation Ability of Zinc–Cobalt Ferrite Nanoparticles Designed for Hyperthermia - Zaid Mukhtar; Jin Nakamura; Toshiki Miyazaki (International Journal of Ceramic Engineering & Science, 2025)
ABSTRACT Magnetic nanoparticles generate heat when exposed to an alternating magnetic field, making them useful as thermoseeds for efficient hyperthermia treatment of deep‐seated cancer inside the body. Among them, the Curie point of zinc–cobalt ferrite can be tuned within the 40°C range by controlling the composition, thereby suppressing excessive temperature increases in the body during treatment. These nanoparticles are also expected to have antibacterial effects. During synthesis, the microstructure and properties can be regulated by adding organic substances. Herein, zinc–cobalt ferrite nanoparticles were synthesized using sol–gel methods with varying amounts of polyvinylpyrrolidone (PVP), and the effects of the synthesis conditions on the microstructure, magnetic properties, and heat generation behavior were investigated. The highest temperature increase of around 60°C was observed for samples prepared with 6 wt% PVP, but it decreased when the concentration was increased to 9 wt%. This was attributed to aggregation and the formation of nonmagnetic compounds.